PERLINDUNGAN HUKUM TERHADAP ANAK DIBAWAH UMUR YANG MENJADI KURIR NARKOBA - A. Muh. Nur. Khaidir; Ahkam Jayadi; Fadli Andi Natsir (Alauddin Law Development Journal, 2019)
Legal protection for children as narcotics criminals is very necessary because remembering the mental and psychological specificity of children is very different from adults. This legal protection is very important in order to protect children's rights so that they can grow, develop, participate optimally in accordance with human dignity, and get protection from violence and discrimination. Legal protection can be applied through the discretion of the National Police and Court Decrees where sanctions for acts of narcotics criminals can be cured physically and mentally without the need for criminal sanctions